2007
DOI: 10.1021/la0633280
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Mediated Grafting of Poly(ethylene glycol) on Polyamide and Polyester Surfaces and Evaluation of Antifouling Ability of Modified Substrates

Abstract: A simple cold plasma technique was developed to functionalize the surfaces of polyamide (PA) and polyester (PET) for the grafting of polyethylene glycol (PEG) with the aim of reducing biofilm formation. The surfaces of PA and PET were treated with silicon tetrachloride (SiCl4) plasma, and PEG was grafted onto plasma-functionalized substrates (PA-PEG, PET-PEG). Different molecular weights of PEG and grafting times were tested to obtain optimal surface coverage by PEG as monitored by electron spectroscopy for ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 41 publications
4
58
0
2
Order By: Relevance
“…The results show approximately 60% reduction in the number of attached Listeria cells from both strains relative to the numbers that can adhere and grow on the unmodified surface; this can most probably be attributed to the brush-like structure of the modification layer. Possibly the effect is similar to what has been demonstrated in other studies [11][12][13], where the brush-like structure of the modifying layer on different surfaces, such as stainless steel, glass, polyamide and polyester, also reduced bacterial adhesion. The effectiveness of these structures against bacterial attachment is caused by steric hindrance that keeps the bacterial cells at a distance from the surface, which results in weakening of the (e.g., van der Waals) interactions [13].…”
Section: Bacterial Adhesionsupporting
confidence: 85%
“…The results show approximately 60% reduction in the number of attached Listeria cells from both strains relative to the numbers that can adhere and grow on the unmodified surface; this can most probably be attributed to the brush-like structure of the modification layer. Possibly the effect is similar to what has been demonstrated in other studies [11][12][13], where the brush-like structure of the modifying layer on different surfaces, such as stainless steel, glass, polyamide and polyester, also reduced bacterial adhesion. The effectiveness of these structures against bacterial attachment is caused by steric hindrance that keeps the bacterial cells at a distance from the surface, which results in weakening of the (e.g., van der Waals) interactions [13].…”
Section: Bacterial Adhesionsupporting
confidence: 85%
“…3). Importantly, for the development of biofilms in the presence of weak adhesion forces, biofilms even form on highly hydrated, polymer brush coatings, which exert very small adhesion forces in the subnanonewton range that were found to be insufficient for adhering bacteria to even realize that they were in an adhering state (35).…”
Section: Discussionmentioning
confidence: 99%
“…Successful routes were physical adsorption, spontaneous assembly of monolayers, electrografting, or photografting onto the surface. [4 -7] Dong et al [8] reported that PEG molecules were successfully grafted onto SiCl 4 -plasmafunctionalized polyamide (PA) and polyethylene terphtalate (PET) surfaces in a PEG degassed liquid phase during 20 h. The surface coverage of PEG was controlled by changing the chain length or the grafting reaction time. Both modified substrates significantly inhibited biofilm formation by Listeria monocytogenes.…”
Section: Introductionmentioning
confidence: 99%